LINGUISTIC AND PERSUASIVE TECHNIQUES IN CONSTRUCTING DIVINE ENTITLEMENT IN NIGERIAN POP MUSIC - Izu, Benjamin Obeghare; Agunbiade, Oyewumi Olatoye (Sanata Dharma University, 2025)
In recent years, Nigerian popular music has moved away from narratives about earning success through hard work. Instead, it now focuses on the narratives that success comes from divine blessings or entitlement. This study explores how Nigerian pop artists use persuasive strategies and linguistic techniques to construct and legitimise expectations of financial breakthroughs as a divine right. Through a textual analysis of Syno’s “Money Fit Me” and Adekunle Gold’s “Pick Up”, the study applied Aristotle’s Rhetorical Appeals, Cialdini’s Principles of Persuasion, and Critical Discourse Analysis to look at how narratives of divine entitlement are shaped. The analysis revealed that the lyrics of Syno focus on communal validation through social proof and reciprocity, demonstrating success as a common expectation, whereas the lyrics of Adekunle Gold employ strong emotional appeal and fear of being left behind, so success appears pressing and deeply personal. These findings show how Nigerian pop music reinforces social perceptions that spiritual devotion and material success are interrelated, and they shape the way people perceive wealth, faith, and upward social mobility in a challenging socio-economic situation. This study contributes to the broader debates on the nexus of language, religion, and popular culture and how they interact with advancing contemporary aspirations in Nigeria.